Artists Making Books : poetry to politics - Porter, Venetia (London : The British Museum Press, 2023)
Sadeghi, Ali Akbar ; Mohassess, Bahman ; Al Said, Shakir Hassan ; Yahya, Nazar ; Dawod, Amar ; Etemadi, Parvaneh ; Malallah, Hanaa ; Tanavoli, Parviz ; Lashai, Farideh ; Ghaib, Ghassan ; Peacock, Jila ; Khonjie, Christine ; Adonis ; Abboud, Shafic ; al-Azzawi, Dia ; Khalil, Mohammad Omar ; Ali, Himat Mohammad ; Boullata, Kamal ; Dalloul, Ziad ; Benanteur, Abdallah ; Nasiri, Rafa ; Kourbaj, Issam ; Koraïchi, Rachid ; Adnan, Etel ; Assadour ; Muraywid, Laila ; Belkahia, Farid ; Morsi, Ahmed ; Tami, Shideh ; Qotbi, Mehdi ; Wou-Ki, Zao ; Khalil, Mohammad Omar ; Ebtekar, Ala ; Métoui, Lassaâd ; Risan, Kareem ; Faraj, Maysaloun ; Al Shammarey, Mohammad ; Chamekh, Nidhal ; Ammar, Héla ; Rabah, Khalil ; Cherri, Ali ; Malas, Khaled ; Sigil Collective ; Malani, Nalini ; Zeeshan, Muhammad ; Al Kadiri, Abed ; Yazigi, Fadi ; Alfraji, Sadik Kwaish ; Obaidi, Mahmoud ; Duben, Ipek ; RRHV ; Shawwa, Zaid ; Shono, Muhannad ; Çetin, Fulya ; Shahroudi, Farkhondeh ; Tavakolian, Newsha ; Matar, Diana ; Zaatari, Akram ; Braithwaite, Al
Artists making books: poetry to politics, British Museum, London, 27 October 2022 to 31 December 2023
boek